Mercosur: What you see is not (always) what you get - Gardini, Gian Luca (European Law Journal, 2011)
Twenty years after its creation MERCOSUR is not a common market yet; its regional parliament has virtually no competence; its first enlargement has been pending ratification for five years. However, MERCOSUR has delivered democratic stability, increased trade flows and international visibility to its members. This article proposes a historical-institutionalist approach to reconcile more and less optimistic appraisals. The historical component suggests that MERCOSUR has evolved according to the evolution of national interests and agendas. The institutional component suggests that the limited and peculiar institutionalisation affects MERCOSUR's functionality and prospects. The article first reviews the historical evolution of MERCOSUR, then concentrates on the current agenda including the accession of Venezuela, the question of the regional parliament and the completion of the customs union, and finally explores the challenges Documentos de Seguridad y Defensa No. 29, Madrid, January 2010 that competing regional blocs pose to MERCOSUR. The conclusion suggests that institutional deepening might take place via parliamentary and judicial developments. © 2011 Blackwell Publishing Ltd..
WiSo-Import:2015-03-26:5132
Keywords: Mercosur